Manual of therapeutics for addictions - Miller, Norman S. (New York : J. Wiley & Sons, 1997)
Here is a much-needed practical guide to the effective diagnosis and treatment of alcohol and drug addictive disorders. Designed to meet the diverse needs of family and primary care physicians, psychiatrists and mental health professionals, and medical students and residents, this authoritative text offers clear, step-by-step recommendations on the selection and application of both pharmacological and psychosocial therapies.
Ch. 21. Alcoholics Anonymous and Narcotics Anonymous in Clinical Practice / John Chappel -- Ch. 22. Treatment Efficacy / Norman S. Miller -- Ch. 23. A Guide to Managed Care, Social Welfare, and Medical Benefits / Kathleen Kim and Joseph A. Flaherty -- Ch. 24. Forensic and Ethical Issues / Amin N. Daghestani.
Includes index.
Keywords: Substance abuse -- Treatment; Substance-Related Disorders -- therapy; Behavior, Addictive -- therapy